ANALISA PERHITUNGAN BALLAST PADA PELUNCURAN MENYAMPING (SIDE LAUNCHING) KAPAL SUNGAI 200GT DI PT. DKB (PERSERO) CABANG SEMARANG - Ariany, Zulfaidah (Gema Teknologi, 2018)
Considering the risk faced in the side launching, limited land from the shipyard so that required calculation and analysis in the implementation of the launching. The purpose of this research is analyzes and counting ballast (a counterweight ) used in a river boat lct 200 GT on the launching of sideways ( side launching ) so that safe and floats can be perfect in water, as nown that the launching of is one of the stages important in the development process the new vessel which have prepared to be operated, formerly preceded by stage first cutting plate ( cutting first steel plate ) and the keel laying ( laying ) keel of a ship. Before the handover of a vessel is carried, a ship will had some sea trial. The results of this research is scientific publication in national journal , as a input for the shipyard to implement the launch sideways safe as well as the basis for students and teachers included in matter basic lecture subjects of case in point in lecture the theory ship building.